Deepening Decentralization within Centrally Led States : The Direction of Local Governance Reforms in Southeast Asia - Bhatti, Zubair K.; McDonald, Lachlan (World Bank, Washington, DC, 2021)
In the early 1990s, a host of unitary states in Southeast Asia began pursuing, at their own pace, the process of decentralizing their systems of governance. The form and function of these reforms were documented in the World Bank's report, East Asia Decentralizes: Making Local Government Work, published in 2005. The analysis in this discussion paper updates the findings and data from this foundational work and widens the lens to new countries embarking on similar reforms. The aim is to chart the overall trajectory of reforms, examine the political dynamics behind them, and help countries locate their place in the process. Each country is taking its own path, shaped by its history, size, and political system, though there are some similarities. In general, reforms are heavily and predictably influenced by political dynamics, managed from the central government, and driven by its priorities. They result in an unsynchronized and, at times, messy transfer of funds, functions, and functionaries to lower levels. Central governments continue to wield considerable influence over subnational governments through a combination of tight political controls, concurrent functional assignments, budgetary measures, and continued bureaucratic control. Nonetheless, with all their limitations, the countries of the region are finding ways to muddle through with the general trajectory toward more, not less, decentralization. In large part, this process is happening organically and incrementally without any big bang reforms and with the direct involvement of central governments. Variously, it is helping to nudge governments toward greater political pluralism, innovation, and improved service delivery within otherwise tightly controlled states. As decentralization deepens, so too does the importance of effective coordination.